2014
DOI: 10.4321/s1135-57272014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de distintas terapias físicas en el tratamiento conservador de la fascitis plantar: revisión sistemática

Abstract: Physical therapies used in the various studies have proven effective to varying degrees either to reduce pain or relieve the symptoms of plantar fasciitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Of the 23 controlled clinical trials, 14 compared the active treatments (monotherapy or combination of several treatment techniques) to a single treatment or placebo. The authors 12 concluded that a combination of several treatment techniques appeared to be more effective than monotherapy. However, due to the heterogeneity of techniques, the different number of sessions, and the diverse duration of treatments, it was impossible to perform a quantitative statistical analysis.…”
Section: Additive Effect Of Therapeutic Ultrasound In the Treatment Omentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 23 controlled clinical trials, 14 compared the active treatments (monotherapy or combination of several treatment techniques) to a single treatment or placebo. The authors 12 concluded that a combination of several treatment techniques appeared to be more effective than monotherapy. However, due to the heterogeneity of techniques, the different number of sessions, and the diverse duration of treatments, it was impossible to perform a quantitative statistical analysis.…”
Section: Additive Effect Of Therapeutic Ultrasound In the Treatment Omentioning
confidence: 99%
“…However, due to the heterogeneity of techniques, the different number of sessions, and the diverse duration of treatments, it was impossible to perform a quantitative statistical analysis. 12 One of the most widely used electrical devices among physical therapists in Israel and worldwide is therapeutic ultrasound. 26,36,41,42,44 Therapeutic ultrasound raises tissue temperature and metabolism, softens the tissues, increases blood circulation, increases the chemical activity of the tissues, increases the permeability of the cell membranes, and modulates the molecular structures and the rate of pulsation and protein production-all potentially affecting the speed of tissue recovery.…”
Section: Additive Effect Of Therapeutic Ultrasound In the Treatment Omentioning
confidence: 99%
“…The treatment-means for PF are divided into surgical and conservative methods. The conservative treatments consist of resting, soft sole supports, heel elevation, night braces keeping the plantar fascia tense at the dorsiflexion, plaster casts, orthosis-type shoe wearing, acupuncture, ultrasound, iontophoresis methods, low density laser application, extracorporeal shockwave therapy, stretching and strengthening exercises, anti-inflammatory (nonsteroid and steroid) medications, cortisone injections and botulinum toxin injection ( Cacchio et al, 2006 ; Cotchett et al, 2014 ; Covey and Mulder, 2013 ; Díaz López and Guzmán Carrasco, 2014 ; Greve et al, 2009 ; Huang et al, 2010 ; Lee et al, 2009 ; Tsai et al, 2010 ; Vahdatpour et al, 2012 ). The conservative therapy is successful 90%–95%.…”
Section: Introductionmentioning
confidence: 99%
“…Non-pharmacological therapies are acknowledged as the first-choice management option for PF, such as biomechanical support, stretching and extracorporeal shockwave therapy (ESWT) 10–13. Pharmacological options are also commonly prescribed (eg, non-steroidal anti-inflammatory drugs (NSAIDS),14 15 botulinum toxin,16–18 platelet-rich plasma injections,19–21 corticosteroid injections 22–24.…”
Section: Introductionmentioning
confidence: 99%